Spatial Epidemiological Pattern of HIV (Asia Pacific Journal of Social and Behavioral Sciences, 2015)
This paper aims to explain the prevalence rate of Human Immunodeficiency Virus worldwide. The data matrix of CIA World Fact Book (2015) was used through new methodologies enclosed in fractal statistical analysis and data mining. After analyzing the data sets of different countries, a pattern was observed regarding the spatial epidemiological spread of HIV. Fractal statistical analysis revealed that the dynamic expansion of the virus is towards the northeastern hemisphere. Data mining further exposed that the spread of HIV follows the pathway along the coastal areas, specifically, following the trading system of the different countries. Moreover, being situated in the tropical environment can contribute directly and indirectly to the HIV prevalence through climate temperatures and agricultural productivity. Through these findings, it is then posited that the HIV incidence is not merely due to sexual activities rather it is also sensitive to the environmental characteristics of diferent countries.
Keywords: Human Immunodeficiency Virus (HIV), spatial epidemiology pattern, Nightingale’s environmental theory, fractal statistical analysis, data mining